Endoscopic Anatomy of Hypotympanum Surgical Implications - Boddepalli, Rajesh; Boddepalli, Sreerama Murthy (Annals of Otology and Neurotology, 2018)
Objective To assess the endomeatal endoscopic morphological anatomy of hypotympanum under local anesthesia and further cadaveric dissection of temporal bone to know complete anatomical details of hypotympanum.Materials and Methods Two hundred six cases of live operations were studied, these included 160 cases of simple dry perforations for myringoplasty and 46 cases of stapedectomy operations. All operations were performed under local anesthesia using a 0-degree, 4-mm endoscope. The hypotympanum was visualized. Twenty wet temporal bones were dissected endoscopically and complete hypotympanic details were studied.Results Out of 206 cases, 94 cases (45%) were found to be type A; 51 cases (25%) were type B and 60 cases (30%) were type C hypotympanum. Wet cadaveric bones were dissected to visualize the transmeatal endoscopic jugular foramen in four levels (levels 1, 2, 3, and 4).
Keywords: hypotympanum; hypotympanotomy; jugular bulb; glomus jugulare; trabeculae; crotch; band of Seibermann; temporal bone dissection